EVALUASI TERHADAP PERLINDUNGAN HUKUM PELECEHAN DAN KEKERASAN SEKSUAL PADA ANAK - De Marrilac, Louisa (UNES Law Review, 2021)
Sexual harassment and violence in general cannot be separated from the life of the general public. Sexual harassment and violence do not only occur among adults and adults, but also among children who are underage (<18 years). Violence and sexual abuse of children is still common among the general public. Violence and sexual harassment are not only experienced by girls in general, but also experienced by boys (pedophilia). Sexual violence and abuse in children is still common, allegedly because it is abuse and misuse by adults. Children are often easy targets for pedophiles because children still don't understand what the deceptions of pedophiles are. Perpetrators of sexual harassment and violence assume that minors are still relatively innocent and the possibility of reporting to the police is very small because they are afraid of threats from the perpetrators. The writing of this journal is intended to better see and evaluate the urgency of existing legal arrangements whether they are in accordance with their relevance and can guarantee legal protection for minors. Journal writing is carried out using a normative approach, namely research conducted by examining library materials and normative legal regulations.